Особливості проектування цифрових пристроїв на базі FPGA Xilinx в САПР Vivado HLx Design Suite - Свид, І. В.; Литвиненко, О. В.; Білоцерківець, О. Г. (ХНУРЕ, 2019)
The new generation of CAD Vivado HLx Design Suite is designed to assist developers in solving the problem - the high complexity of obtaining FPGA tracing with a volume of hundreds of thousands and millions of logic cells in a reasonable time frame and with high quality.
Keywords: ПЛІС; Vivado; САПР; HDL; Xilinx